Development and validation of an easy-to-use risk assessment tool for cumulative low back loading: The Lifting Fatigue Failure Tool (LiFFT). (September 2017) - Gallagher, Sean; Sesek, Richard F.; Schall, Mark C.; Huangfu, Rong
Abstract: Recent evidence suggests that musculoskeletal disorders (MSDs) may be the result of a fatigue failure process in affected tissues. This paper describes a new low back exposure assessment tool (the Lifting Fatigue Failure Tool [LiFFT]), which estimates a "daily dose" of cumulative loading on the low back using fatigue failure principles. Only three variables are necessary to derive the cumulative load associated with a lifting task: the weight of the load, the maximum horizontal distance from the spine to the load, and the number of repetitions for tasks performed during the workday. The new tool was validated using two existing epidemiological databases: the Lumbar Motion Monitor (LMM) database, and a database from a U.S. automotive manufacturer. The LiFFT cumulative damage metric explained 92% of the deviance in low back disorders (LBDs) in the LMM database and 72–95% of the deviance in low back outcomes in the automotive database (depending on the outcome measure). Thus, LiFFT is practitioner friendly and its cumulative damage metric highly related to low back outcomes. Highlights: A practitioner friendly risk assessment tool for manual lifting activities based on fatigue failure theory is presented. The tool requires only load weight, horizontal distance to the load, and the daily number of repetitions for each task. The cumulative load associated with multiple lifting tasks can be easily summed to get a "daily dose" of exposure. The cumulative damage metric demonstrated dose-response relationships with low back outcomes from two epidemiology studies. The strong relationship between our fatigue failure metric and back outcomes suggests a fatigue failure based etiology.